Relationship Between Executive Functions and Reading Skills in Adolescence: Evidence from Students Aged 14 to 20 in Bogotá - Reyes Gavilán, Pablo Alexander; Robayo Huertas, Britney Carolina; Rodríguez Romero, Juan Diego; Paredes Martínez, Juan Sebastián; Aguilar Mejía, Óscar Mauricio; Alonso Díaz, Santiago; Gómez Soler, Silvia Consuelo; Rojas Rincón, Carmen Edilma; Marulanda Páez, Elena (Revista de Investigación en Logopedia, 2026)
Reading comprehension in adolescence depends not only on linguistic proficiency but also on higher-order cognitive processes, among which executive functions (EF) play a key role. This study aimed to examine the relationship between EF and reading skills in a sample of 136 students from Bogotá (Colombia), aged between 14 and 20 years. A cross-sectional observational design was employed using the PROLEC-SE-R battery to assess reading skills at the lexical, syntactic, and semantic levels, along with computerized neuropsychological tests to measure sustained attention (SART), working memory (Digit Span), and non-verbal abstraction (Raven’s Progressive Matrices). Correlational analyses revealed significant associations between performance on EF tasks and various components of reading. Specifically, sustained attention and inhibitory control were linked to a greater ability to detect syntactic and semantic inconsistencies, while working memory was associated with more accurate processing of complex grammatical structures and overall text comprehension. These findings suggest that EF contribute in distinct ways to reading processes, reinforcing their role in grammatical organization, attentional regulation, and meaning integration.
Keywords: reading skills; PROLEC-SE-R; executive functions; sustained attention; working memory; non-verbal abstraction